Utilisation of Library Information Resources among Generation Z Students: Facts and Fiction - Oghenere, Gabriel Salubi; Ondari, Ezra Okemwa; Nekhwevha, Fhulu (My University, 2018)
Generation Z was the foremost generation to have prevalent access to the Internet from an early age. Technology has strongly influenced this generation in terms of communication, education and consequently their academic information behaviour. With the next generation of scholars already being trained, in a decade, most of the researchers will be mainly digital natives. This study sought to establish the library information resources use pattern in relation to users’ preferred information media in order to render better academic information services to library users. A total of 390 respondents were surveyed at the Nelson Mandela University and the University of Fort Hare using quantitative and qualitative methods. Most of the respondents, 82.3%, were aged between 18 and 23 years; while the average library use time was two hours daily. The most utilised library resource is the Wi-Fi with e-books and e-journals found to be lowly utilised. Records from the E-librarians revealed that undergraduate students account for no more than 6% of total users of electronic databases with 62.3% of the respondents preferring print information resources. Better understanding of library users’ demographics and information media preference is essential in proving the right kind of information services to Generation Z library users.
Keywords: Generation Z; Library information resources; Library use; Undergraduate students